Global shocks to fertilizer markets: Impacts on prices, demand and farm profitability - Vos, Rob; Glauber, Joseph W.; Hebebrand, Charlotte; Rice, Brendan (Elsevier, 2025)
During 2021–2022, spiking fertilizer prices raised fears that fertilizer application would drop around the world, leading to lower crop production, higher food prices, and greater food insecurity. Even writing mid-2024, a paucity of data impedes a full assessment of how the underlying global market shocks may have affected farmers and food production around the world. Using proxy indicators for fertilizer demand and farm profitability, we find that despite the steep increase in input costs, global demand for fertilizer fell only modestly during the 2022–2023 crop cycle, suggesting many (commercial) farmers were able and willing to absorb increased input costs in the context of generally good harvest prospects and, at the time, high crop prices. However, we also find the fertilizer price spikes have not been felt equally, with many farmers in Africa estimated to have been affected more adversely, even though with varied impacts also amongst those farmers.